Strategi Pemerintah Kota Yogyakarta dalam Menerapkan Kebijakan Zero Sampah Anorganik Berkelanjutan - Nursamsiyah Nursamsiyah; Zuly Qodir (Society, 2024)
This research aims to analyze the implementation of the Zero Inorganic Waste policy enacted by the Yogyakarta City Government, focusing on waste sorting strategies, infrastructure support, and challenges encountered in managing inorganic waste. The qualitative methodology involves field observations, in-depth interviews, and focus group discussions with various stakeholders. The research findings indicate that while this policy has successfully raised public awareness about waste separation, significant challenges remain, such as low public participation, limited infrastructure, and insufficient education efforts. Therefore, the government must increase resource allocation for waste management infrastructure and develop more effective educational programs to encourage behavioral change. This study’s contribution to urban waste management literature lies in its emphasis on the importance of a participatory and systematic approach to waste management and the need for public behavioral change to achieve sustainability goals. The conclusions of this study provide valuable insights for policymakers and practitioners in formulating more effective waste management strategies in Yogyakarta and other urban areas. This research also offers substantial theoretical contributions, particularly regarding the importance of participatory and systematic approaches in urban waste management and the necessity for societal behavioral changes to achieve sustainability objectives.